Financial Independence 101: A Blueprint for Early Retirement - Clara Neltje Meini Rotinsulu; Muhammad Sani Kurniawan; Ananta Dian Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the determinants of early retirement preparedness within the context of Bank Sulteng, focusing on the roles of income, expenses, and investments. Using a quantitative approach and Smart PLS analysis, data from a sample of 100 bank customers were analyzed to explore the direct and indirect effects of these variables on early retirement preparedness. The results indicate that income significantly influences both investment decisions and early retirement preparedness, highlighting its crucial role in shaping individuals' financial trajectories. Moreover, investments emerged as a significant determinant of early retirement preparedness, underscoring the importance of strategic investment planning. However, while expenses showed a direct significant impact on early retirement preparedness, their indirect effect through investments was not statistically significant. These findings provide valuable insights for individuals, financial institutions, and policymakers aiming to enhance financial literacy and promote effective retirement planning strategies.